Case report: Reconstruction of distal medial tibial epiphysis using iliac crest apophyseal autograft - Zhu, Chengming; Shi, BaoJie; Rai, Saroj; Zhong, Haobo; Tang, Xin (Frontiers in Pediatrics, 2022)
Background: Salter type VI physeal fracture is a rare injury. This case study aims to present a novel method for treating a rare entity of Salter type VI physeal injury of the medial malleolus. Case presentation: A 6-year-old boy with the Salter type VI physeal injury was successfully treated with the two-stage procedure. In the first stage, he was treated with an administration of intravenous antibiotics, a series of debridement and lavage followed by a skin graft that left a defect in a medial malleolus. In the second stage, an autogenous iliac crest apophyseal graft was transplanted to reconstruct the medial malleolus and hold the ankle joint by an external fixator. An additional anticipatory Langenskiold procedure was performed for a physeal bar resection. Although the complete similar development of medial malleolus compared to the contralateral side was not evident at the last follow-up, the functional and cosmetic outcomes were satisfactory. Conclusion: This technique for the reconstruction of medial malleolus with an application of an external fixator is a novel reconstruction method in treating Salter type VI physeal injury in medial malleolus in children. Further study regarding the effectiveness of this technique in such type of fracture pattern is warranted.